The Pharmacological Effects of Kappa Carrageenan on Different Human Cell Lines and Genomic DNA: An in vitro study - Aseel J. Ali; Hajer I. Abdulla; Marwan S. Al-Nimer (College of Pharmacy University of Baghdad, 2021)
Carrageenan extract is a compound of sulfated polyglycan that is taken out from red seaweeds. Being hydrocolloid in nature, carrageenan has gelling, emulsifying and thickening properties allowing it to be commonly used in the oral healthcare products and cosmetics. Due to its bioactive compounds, carrageenan has been shown to have antimicrobial, antiviral, and antitumor properties. The purpose of this work is to study the probable use of carrageenan on the diseases that are related to oral cavity and on the genomic DNA in in vitro experimental model In this study, the effects of k-carrageenan on four different cell lines related to the cancer and normal cells which cultured on selective media were done. Moreover, the effect of K-carrageenan on the DNA molecule using an in vitro model was investigated in order to explain the antiproliferative effect of carrageenan. Kappa-carrageenan inhibited the cancer cell growth and fibroblast cell lines growth (in vitro) experimental model. In additionk-carrageenan solution completely and significantly damaged the DNA molecule by the evidence that the mean ± SD absorbance of the mixture of k-carrageenan and DNA solution is 0.0 ± 0.0.  This study shows that the k-carrageenan pharmaceutical preparations exert biological activities as anticancer in vitro studies.